1994
DOI: 10.3109/00016349409072513
|View full text |Cite
|
Sign up to set email alerts
|

Use of pap‐smears in a population without a mass screening program

Abstract: More than half of the women aged 50 and above have no smears or smears less than one every third year. This proportion increases with age. The use and distribution of smears by age is still far from the situation expected in an organized screening program although a slight amelioration was observed through the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Reliable information about patients' delay is not available in our study; and to our knowledge, no other studies have related patients' delay to parity. Since it is known that cervical cytologic examinations are often performed during family planning consultations and in relation to antenatal care,31 and that unmarried women have a lower attendance rate,32 it is possible that there is a decreased attendance in gynecologic examinations among nulliparous women in general. It has been reported that patients having regular check‐ups have a significantly lower delay 33.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable information about patients' delay is not available in our study; and to our knowledge, no other studies have related patients' delay to parity. Since it is known that cervical cytologic examinations are often performed during family planning consultations and in relation to antenatal care,31 and that unmarried women have a lower attendance rate,32 it is possible that there is a decreased attendance in gynecologic examinations among nulliparous women in general. It has been reported that patients having regular check‐ups have a significantly lower delay 33.…”
Section: Discussionmentioning
confidence: 99%
“…However, these observations did not lead to early establishment of an organised screening programme, even though such programmes were developed in neighbouring Nordic countries during the 1960s and 1970s . In Norway, cytology became widespread during the 1970s, but without centralised management, the opportunistic screening activity was not optimally allocated in the target population . After a pilot in two counties in 1992–1994, the nationally organised population‐based programme was launched in 1995 with centralised monitoring, management functions and individual reminders to those overdue for their screening tests .…”
mentioning
confidence: 99%
“…9 In Norway, cytology became widespread during the 1970s, but without centralised management, the opportunistic screening activity was not optimally allocated in the target population. 10,11 After a pilot in two counties in 1992-1994, the nationally organised population-based programme was launched in 1995 with centralised monitoring, management functions and individual reminders to those overdue for their screening tests. 12 Organising the screening activity has led to a more efficient use of resources and further reductions in cervical cancer incidence and mortality.…”
mentioning
confidence: 99%
“…During the period 1965-85, however, a 10-fold increase in the annual number of Pap smears was observed (Norges Offentlige Utredninger, 1987). This was due mainly to frequent opportunistic Pap testing, especially of women of child-bearing age (Forsmo et al, 1994). In most of the other Nordic countries, organized screening was introduced about 30 years ago, and cervical-cancer incidence has been decreasing since the mid-1960s (Hakama, 1982).…”
mentioning
confidence: 99%